An analysis of the substantivity of hydrolysed reactive dyes and its implication for rinsing processes. (2nd November 2012) - Ferus‐Comelo, Martin
<x xml:space="preserve">Abstract</x> Substantivity plays a key role in dyeing processes, for dye exhaustion and fixation as well as for dye removal during rinsing. The latter is especially relevant for reactive dyes when the hydrolysed dye has to be removed from the fibre. The substantivity of the hydrolysed form of 46 commercially important reactive dyes was analysed at two temperatures for a wide range of dye amounts, pH values and electrolyte concentrations. The results showed that substantivity was highly dye‐specific and varied, for each variable analysed, almost within the entire theoretically possible range of values. Substantivity values correlated best with the number of sulphatoethylsulphone groups in the dye molecule and dye solubility in the presence of sodium chloride. Sensitivity to electrolyte, pH, dye amount and temperature broadly correlated with each other, implying that a reduction in electrolyte concentration and an increase in pH and temperature are more beneficial in the removal of highly substantive reactive dyes. Some dyes remained highly substantive even at 90 °C, indicating that dye removal in industrial processes, too, would be difficult. For dyes with little substantivity, however, wash baths at the boil do not appear to be necessary, neither is the significant removal of electrolyte before rinsing at elevated temperature.